Sinbad - Hardy-Gould, Janet (Oxford University Press, 2005)
Sinbad the sailor spends many years at sea. He visits strange countries, meets some strange people and some very frightening animals. He is sometimes rich, sometimes poor and always in danger. But all the time he is learning for his adventures, until finally he returns home to Baghdad, an older and wiser man